The Implications of Breastfeeding Self-Efficacy on Prelacteal Feeding in First Week of Birth - Mertasari, Luh; Sugandini, Wayan; Giri, Ketut Espana (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
Breastfeeding is a special and joyful event that most mothers and their babies experience. Exclusive breastfeeding (breastfeeding only for babies until they are six months old) is an activity that is very beneficial for both mother and baby. The low achievement of exclusive breastfeeding often begins with giving prelacteal intake in the first days of the baby's life because of the low understanding of the baby's mother about the importance of breastfeeding. This study links the relationship between breastfeeding self-efficacy and prelacteal feeding in the first week of birth. This type of research is correlational with a cross-sectional approach. The population in this study were breastfeeding mothers in the first week of the baby's birth; the number of samples was 50 people with purposive sampling technique. The data was collected using the BSE-SF questionnaire and observation—data analysis with univariate and bivariate chi-square tests to determine the relationship between the two variables. The study results with a p-value of 0.000 0.05, so it was concluded that there was a relationship between breastfeeding self-efficacy and the provision of prelacteal nutrition in the first week of birth. This research can then be used to reference further breastfeeding guidance strategies.